2006
DOI: 10.1177/112067210601600614
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Retinitis Pigmentosa in Urban and Rural Adult Chinese: The Beijing Eye Study

Abstract: Retinitis pigmentosa with typical fundus appearance and functional loss may be present in about 1 out of 1000 elderly Chinese in Northern China. Calculated for the whole population in China, the figure would be 1.3 million patients with retinitis pigmentosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 5 publications
2
52
2
Order By: Relevance
“…Male preponderance was present in the studies reported from Beijing, Denmark and Nigeria. 8,13,17 No statistically significant regional preponderance (rural vs. urban) was noted in the subjects with RP in our study. Notably 2 (15.38%) subjects were relatively asymptomatic whereas others complained of decrease of vision.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Male preponderance was present in the studies reported from Beijing, Denmark and Nigeria. 8,13,17 No statistically significant regional preponderance (rural vs. urban) was noted in the subjects with RP in our study. Notably 2 (15.38%) subjects were relatively asymptomatic whereas others complained of decrease of vision.…”
Section: Discussioncontrasting
confidence: 63%
“…Recently published report from Beijing eye disease study reports prevalence of RP to be 1 in 1000 approximately in the 40 year above population. 8 Prevalence rates as described in other studies like that of Hu et al, Bunker et al, and Bundey et al, were 1:3784, 1:4756 and 1:4869 respectively. 9−11 A nationwide registration of Danish patients with retinitis pigmentosa provided 1890 persons diagnosed during the period 1850-1989, reflecting a prevalence rate of 1:3943.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…On clinical examination, the retina of aVected individuals commonly shows pallor of the optic disc, attenuated retinal vessels, atrophy of the retinal pigment epithelium (RPE) and pigmentary deposits within the retina. The population-wide prevalence of RP varies in diVerent regions and ranges from 1:4,000 to 1:1,000 in diVerent parts of the world (Bundey and Crews 1984;Bunker et al 1984;Dandona et al 2001;Xu et al 2006). Non-syndromic RP occurs in autosomal dominant, recessive and X-linked forms with over 60 genes identiWed till date.…”
Section: Introductionmentioning
confidence: 96%
“…elderly Chinese people in Northern China [4]. RP can be transmitted as a dominant, recessive, X-linked, or non-Mendelian trait [5].…”
mentioning
confidence: 99%